Wrestling fun - Meister, Cari (2021)
"Wrestling is cool to watch, but it's even more fun to do! Kids can get out on the mat by learning the rules of the sport, the gear and skills needed to wrestle, and the importance of good sportsmanship. A skill-building activity helps readers get in on the fun"--
What is wrestling? -- What do I need to wrestle? -- Where do I wrestle? -- How do I learn to wrestle? -- How can I be good sport? -- Skill builder: on your feet.
Includes bibliographical references and index.
Ages 6-8
Grades 2-3
Keywords: Wrestling -- Juvenile literature